Liposomal clodronate combined with Cisplatin or Sorafenib inhibits hepatocellular carcinoma cell proliferation, migration and invasion by suppressing FOXQ1 expression - Zhou, Yilong; Chen, Yuan; Ma, Chunyang; Shao, Bingfeng; Zhang, Feng (Cellular and Molecular Biology, 2020)
The purpose of this study was to investigate the effect of liposomal clodronate combined with Cisplatin or Sorafenib on the FOXQ1 expression and biological function of hepatocellular carcinoma cell lines. The expression of FOXQ1 was determined in normal hepatic cell line and hepatocellular carcinoma cell lines using quantitative real-time polymerase chain reaction (qRT-PCR). HepG2 and MHCC97H cells were administered low, medium and high concentrations of cisplatin (3, 5 and 7 Î¼g/ml) or Sorafenib (2, 7 and 20 Î¼g/ml) in combination with liposomal clodronate (LC, 20Î¼g/ml), and the expression of FOXQ1 in each group was determined. Cell migration, MTT and transwell assays were used to determine the effects of the treatments on biological functions of HepG2 and MHCC97H cells. qRT-PCR showed that the expression of FOXQ1 mRNA was higher in the four hepatocellular carcinoma cell lines than in normal cells, and the expression of FOXQ1 mRNA in HepG2 and MHCC97H cells were more dominant. All the tested doses of Cisplatin, but only high dose Sorafenib down-regulated the expression of FOXQ1. However, Sorafenib at low and medium concentrations had no significant effect on the expression of FOXQ1. When Cisplatin or Sorafenib was administered in combination with LC, the expression level of FOXQ1 was significantly reduced. Cell migration, MTT and transwell assays showed that proliferation, migration and invasion were inhibited when each drug was administered alone, but was stronger when the drugs were combined with liposomal clodronate. Liposomal clodronate combined with Cisplatin or Sorafenib down-regulates the expression of FOXQ1 in HepG2 and MHCC97H hepatoma cells, and inhibits their proliferation, migration and invasion.